Argentina: From the small screen to the platforms. The rebirth of television fiction - Kirchheimer, Monica Susana (2023)
2022 was a year dominated by the return of the reality show par excellence: Big Brother -since October- and the World Cup. These two events were the most watched andgenerated an interesting debate about the topics, modes and programs that attractaudiences to broadcast television. In addition, only two fictions of national production were released on open television channels, while, as has been reported inprevious years, national fictions for streaming platforms release their first chapter inlinear television spaces. This premiere works as a sort of caller towards novelties inon-demand viewing spaces. In this scenario, the telenovelas released on open television during the year (El Primero de Nosotros and La 1-5/18 Somos Uno4) did not end up meeting the expectations initially generated.